Reorganization of the flagellum scaffolding induces a sperm standstill during fertilization - Martina Jabloñski; Guillermina M Luque; Matias Gomez Elias; Claudia Sanchez Cardenas; Xinran Xu; Jose L de La Vega Beltran; Gabriel Corkidi; Alejandro Linares; Victor Abonza; Aquetzalli Arenas-Hernandez; María DP Ramos-Godinez; Alejandro López-Saavedra; et al. (eLife)
Mammalian sperm delve into the female reproductive tract to fertilize the female gamete. The available information about how sperm regulate their motility during the final journey to the fertilization site is extremely limited. In this work, we investigated the structural and functional changes in the sperm flagellum after acrosomal exocytosis (AE) and during the interaction with the eggs. The evidence demonstrates that the double helix actin network surrounding the mitochondrial sheath of the midpiece undergoes structural changes prior to the motility cessation. This structural modification is accompanied by a decrease in diameter of the midpiece and is driven by intracellular calcium changes that occur concomitant with a reorganization of the actin helicoidal cortex. Midpiece contraction occurs in a subset of cells that undergo AE, and live-cell imaging during in vitro fertilization showed that the midpiece contraction is required for motility cessation after fusion is initiated. These findings provide the first evidence of the F-actin network’s role in regulating sperm motility, adapting its function to meet specific cellular requirements during fertilization, and highlighting the broader significance of understanding sperm motility.